Glucocorticoid receptor binds half sites as a monomer and regulates specific target genes - Schiller, Benjamin J (BioMed Central, 2014)
BACKGROUND: Glucocorticoid receptor (GR) is a hormone-activated, DNA-binding transcriptional regulatory factor that controls inflammation, metabolism, stress responses, and other physiological processes. In vitro, GR binds as an inverted dimer to a motif consisting of two imperfectly palindromic 6 bp half sites separated by 3 bp spacers. In vivo, GR employs different patterns of functional surfaces of GR to regulate different target genes. The relationships between GR genomic binding and functional surface utilization have not been defined. RESULTS: We find that A477T, a GR mutant that disrupts the dimerization interface, differs from wild-type GRα in binding and regulation of target genes. Genomic regions strongly occupied by A477T are enriched for a novel half site motif. In vitro, GRα binds half sites as a monomer. Through the overlap between GRα- and A477T-bound regions, we identify GRα-bound regions containing only half sites. We further identify GR target genes linked with half sites and not with the full motif. CONCLUSIONS: Genomic regions bound by GR differ in underlying DNA sequence motifs and in the GR functional surfaces employed for regulation. Identification of GR binding regions that selectively utilize particular GR surfaces may discriminate sub-motifs, including the half site motif, that favor those surfaces. This approach may contribute to predictive models for GR activity and therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-014-0418-y) contains supplementary material, which is available to authorized users.